The challenges of the Brazilian creative and cultural sectors during and after the covid-19 pandemic - Silva Junior, João Roque da (Revista Extraprensa, 2021)
This article discusses some challenges that the Brazilian cultural and creative sectors had to face during the COVID-19 pandemic and, possibly, during the following years. For this, after a brief contextualization of the formation of the international discourse on culture, creativity, and development, which allowed verifying, in general terms, its resonance in Brazilian cultural policies, we discussed some available data on the Brazilian cultural sector in the first and second semesters of 2020. Then, we discussed the implementation of the Aldir Blanc Law and the challenges surrounding cultural policies. One of the most worrying aspects was the profound silence about the role of the cultural and creative sector for the Sustainable Development Goals.